Peran Kepemimpinan Rasulullah dalam Pengembangan Pendidikan Islam dan Warisan Peradaban Islam - Putri Wulandari; Samsu Alam.L; Yulia Afriliana; Jamrizal Jamrizal; Samsu Samsu (Hikmah : Jurnal Studi Pendidikan Agama Islam, 2025)
The leadership of the Prophet Muhammad SAW in Islamic education is a very relevant example to this day. Through his leadership characteristics which include honesty, trustworthiness, gentle firmness, and noble morals, the Prophet Muhammad SAW succeeded in transforming the divided Arab society of Jahiliyah into one people united in Islamic values. He led with a clear vision and mature strategy, creating an education system that prioritizes the development of character, morals, and knowledge. The Islamic education inherited by the Prophet Muhammad SAW not only includes religious knowledge, but also general knowledge that gave birth to various great scientists during the golden age of Islam. The legacy of his leadership is evident in his broad influence on the development of Islamic civilization. His success in establishing the Islamic Khilafah State and introducing the values ​​of justice, compassion, and the spirit of seeking knowledge became the foundation for the development of science that was very advanced at that time. Therefore, the principles of the leadership of the Prophet Muhammad SAW are not only relevant in a historical context, but can also be implemented in facing global challenges in the modern era, by emphasizing the importance of education, justice, and integrity.